The Effects of Family-Business Related Characteristics and Strategic Planning on Corporate Entrepreneurship - ESER, GÜL (ELSEVIER SCIENCE BV, 2012)
This study investigates the relationships between family-business related characteristics, strategic planning and corporate entrepreneurship in family firms. The effects of four characteristics (willingness to change, generational involvement, perceived technological opportunities, competitive aggressiveness) one of which (competitive aggressiveness) that has not been considered before is examined. Findings suggest that all the factors, except for generational involvement have a positive effect on corporate entrepreneurship. Willingness to change is found to have the most important effect on corporate entrepreneurship. Also strategic planning found to have a positive effect on corporate entrepreneurship. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 8th International Strategic Management Conference
Keywords: Family-business related characteristics; willingness to change; generational involvement; perceived technological opportunities; competitive aggressiveness; strategic planning; corporate entrepreneurship; ORIENTATION; INVOLVEMENT; PERFORMANCE; GROWTH; FIRMS